Consumer Protection in Electronic Transactions: Normative Gaps and Legislative Reform in Indonesian Digital Commerce Law - Amirullah; Rizki Tri Anugrah Bhakti; Dwi Afni Maileni; Agus Riyanto (Faculty of Law, University of Merdeka Malang, 2025)
donesia's digital economy has expanded at a pace that fundamentally outstrips the adaptive capacity of its consumer protection legal framework. This study examines the normative adequacy of Indonesia's legislative architecture governing consumer protection in electronic transactions, with particular attention to the structural gaps produced by the interaction of Law Number 8 of 1999 concerning Consumer Protection (UUPK), Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) as amended by Law Number 1 of 2024, Government Regulation Number 80 of 2019 concerning Trade through Electronic Systems, and the newly enacted Law Number 27 of 2022 concerning Personal Data Protection (UU PDP). Employing a normative juridical method with statutory, conceptual, and comparative approaches, this study identifies three critical normative gaps: the definitional inadequacy of pelaku usaha under the UUPK, which fails to encompass digital marketplace platform operators; the absence of pre-contractual transparency obligations governing algorithmic standard form contracts; and the structural incompatibility of existing dispute resolution mechanisms with the tripartite architecture of digital marketplace commerce. Comparative analysis of the European Union's Digital Services Act and China's E-Commerce Law of 2018 furnishes doctrinal reference points for reform. This study concludes that effective consumer protection in Indonesian digital transactions requires targeted amendments to the UUPK, structural integration of UU PDP into the consumer protection framework, and the establishment of a dedicated Online Dispute Resolution mechanism accessible to consumers without legal representation.